(untitled) (Bangladesh Journal of Agricultural Research, 2019)
A field experiment on broccoli taking the hybrid variety ‘Green Magic’ was conducted with seven treatments [T1 = 100% recommended dose of inorganic fertilizer(100-35-60-18-2-1.2 kg/ha of N-P-K-S-Zn-B+Cowdung (CD) @5 t/ha), T2 = 50% inorganic fertilizer recommended dose + Mustard Oil Cake(MOC) @ 1.5 t/ha, T3 = 50% inorganic fertilizer of recommended dose + CD @ 10 t/ha, T4 = 50% inorganic fertilizer of recommended dose + Poultry Manure (PM) @ 6 t/ha, T5 = 25% inorganic fertilizer of recommended dose + MOC @ 3 t/ha, T6 = 25% inorganic fertilizer of recommended dose + CD @ 15 t/ha, T7 = 25% inorganic fertilizer of recommended dose + PM @ 12 t/ha] at the Horticultural Research Farm of Bangabandhu Sheikh Mujibur Rahman Agricultural University, Salna, Gazipur during the period from September 2015 to February 2016. The aim of the study was to standardize the organic manure and inorganic fertilizers of broccoli for proper growth and yield. The experiment was laid out in a Randomized Complete Block Deign with three replications. All the parameters studied were significantly influenced by different treatments. The maximum plant height (62.20 cm) and canopy spread (64.67 cm), maximum number of leaves/plant (30.23) and average size of leaves (738.1 cm2) and length of terminal head (15.57 cm) were found in T5 which was statistically similar with T7. The diameter of stems (3.87 cm), terminal head diameter (16.17 cm), terminal head weight/plant (424.6 g), number of lateral heads/plant (4.86), weight of lateral heads/plant (155.5 g), yield/plot (11.60 kg/6m2), yield (19.34 t/ha) were found the highest in T7 which was statistically similar with T5. Gross return and net return were the highest in T7and benefit cost ratio (BCR) was also maximum (3.64) in T7. Bangladesh J. Agril. Res. 44(1): 13-26, March 2019